CARACTERIZAÇÃO DA PRODUÇÃO CIENTÍFICA SOBRE BIM DE 2009 A 2017: ANÁLISE DOS TRABALHOS PUBLICADOS NO ENTAC, IGLC E REVISTA G&TP - Borges, Rodrigo Magalhães Siqueira; Barros Neto, José de Paula (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In civil construction sector, there are still many reports of inefficiency of several activities related to the sector. In an attempt to achieve a more efficient planning, Building Information Modeling (BIM) has become a strong ally by allowing decisions to be made early, avoiding unproductive activities in construction, such as reworking. It is noticed that studies realization directed to BIM is increasing, offering much valuable information to scientific environment. However, because it is a very broad topic, there are researches that involve different subjects and environments, often making it difficult to search for a specific topic. From this approach, this paper proposes a bibliometric research of BIM papers, as well as their interpretation, published in the "Encontro Nacional de Tecnologia do Ambiente Construído" (ENTAC), International Group for Lean Construction (IGLC) and "Gestão & Tecnologia de Projetos" (G&TP) magazine between the years 2009 and 2017, in order to understand some features, like: which environments are most studied, which topics are most discussed and what are the limitations in applied researches. All papers that have the acronym "BIM" in their title were studied among the years cited. At the end of the research, 106 papers were analyzed.